Multivariable pid control tuning based on optimization technique for wastewater treatment plant - Selamat, Nur Asmiza (2013)
Control designs of wastewater treatment plants (WWTP) become significant nowadays. This is due to the changes in parameters and influent characteristics. WWTP involve a multivariable process which is highly complex and tuning of the control is not easy. In this work, proportional-integral-derivatives (PID) controllers is used. Through a proper tuning of PID controller will result in better closed loop performance of the system. The PID tuning parameters used in this work have been obtained by optimization technique. Two types of optimization method used; particle swarm optimization (PSO) and genetic algorithm (GA) techniques. The tuning parameters have been obtained and the multivariable PID control has been applied to WWTP. The simulation results show better improvement in closed loop performance.